Influence of creativity and resilience on nursing staff polychronicity - Castelo-Rivas, Walter Patricio (2023)
Objective. To determine the level of influence of creativity and resilience in the polychronicity of nurses who work in emergency areas in public and private hospitals in Santo Domingo de los Colorados, Ecuador. Methods. The study was quantitative, of correlational scope and cross-sectional design. The study population consisted of health professionals in the nursing area of public hospitals and the sample consisted of 411 nurses. A survey with 15 questions was used for data collection and the statistical tests were developed through exploratory factor analysis (EFA), confrmatory factor analysis (CFA) and structural equation modeling (SEM); developed through SPSS 21 and AMOS 24. Results. Statistical analyses identifed that creativity has a significant influence on the polychromicity of nurses, while resilience has a moderate influence. Conclusions. It is concluded that the ability to develop several activities at the same time or polychronicity, within the work activities in emergency areas, is conditioned by the level of creativity that these health professionals have. In turn, being continuously cared for by patients with severe disease or life-threatening illnesses has led nurses to become resilient in these situations; however, this does not condition their levels of creativity.